Upaya Meningkatkan Hasil Belajar PJOK pada Materi Bulu Tangkis Melalui Metode Demonstrasi di Kelas V SDN 65/X Sungai Beras Semester Genap Tahun Pelajaran 2022/2023 - Eko Purwono (Departement of Mathematics Education, 2022)
This study aims to find out and discuss the learning outcomes of physical education and sports and health of students using the demonstration method. This research is a type of classroom action research. The research was carried out in the even semester of the 2022/2023 school year in class V SDN 65/X Sungai Beras with a total of 28 students. The research procedure is in two cycles. Each cycle consists of two meetings where each meeting includes planning, action, observation, and reflection. Data collection techniques with observation, documentation, and tests. Data analysis carried out in this study was the percentage of learning outcomes. The results of this study indicate that the use of the Demonstration method with the act of giving rewards can improve learning outcomes in Physical Education, Sports and Health in class V SDN 65/X Sungai Beras